Enigmas from the past: M’Intosh’s (1885) annelidicolous copepods from the voyage of H.M.S. Challenger - Huys, Rony (Zootaxa, 2016)
The type material of four monotypic genera, Leaniricola, Oestrella, Praxillinicola and Trophoniphila (Copepoda, Cyclopoida), described by M’Intosh (1885) from deep water polychaete hosts collected during the H.M.S. Challenger expedition, is re-examined. Leaniricola rotundata M’Intosh (1885) is removed from its floating status as species inquirenda in the Nereicolidae and fixed as the type of a new family, Leaniricolidae fam. nov., based on the presence of an oral cone and massive, three-dimensionally expanded, mandibular gnathobases which are used to anchor the parasite in the parapodial integument of its host. The ectoparasitic Praxillinicola kroyeri (M’Intosh, 1885), previously treated as a species inquirenda in the Clausiidae, cannot be placed in any of the currently recognized poecilostome families and is here fixed as the type of a new family, Praxillinicolidae fam. nov. Females are characterized by unique bilobate antennules, contained within anterior sockets shared with the reduced antennae, and by paired labral hooks, both of which probably serve as auxiliary attachment organs. Despite its highly transformed body P. kroyeri has retained the plesiomorphic condition of the female genital system, with the gonopores positioned dorsolaterally and the paired copulatory pores lying close together on the midventral surface. The position of the mesoparasitic Trophoniphila bradyi M’Intosh, 1885 in the Bradophilidae is confirmed based on the presence of a median copulatory pore in the female, the disproportionately large egg sacs, the shape of the ectosoma and host utilization. Both sexes of Bradophila pygmaea Levinsen, 1878 are re-examined and the male is redescribed in detail. Flabellicola Gravier, 1918a is treated as a genus incertae sedis in the Bradophilidae. The anal prominence, previously reported in the female of Oestrella (= Melinnacheres) levinseni M’Intosh, 1885 (Saccopsidae), proved upon re-examination to be one of the paired genital apertures. The third and fourth pairs of appendages reported in male saccopsids are here interpreted as the maxillae and maxillipeds, respectively.